(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
One of the key of territories socio-economic development and strengthening of local self-government in Ukraine is to provide the territories budgetary efficiency. The lack of necessary financial providing for state delegated powers and the inability to financing its own development strategies show the inefficient revenue generation and expenditure financing at the local level. It indicates the incompleteness of the transformation processes in our country. So, it is necessary to deeper investigation of the specific aspects of decentralization in Ukraine. The purpose of this article is to investigate the influence of decentralization on the local self-government budgetary effectiveness. It is important to form economic essence of the territories efficiency category within the decentralization and to form the mechanism of its providing. Budget efficiency of territories is a complex economic category that includes the efficiency of local budgets revenue and expenditure. Expenditure are very important as the way of satisfaction of socio-economic functions of local self-government and revenue are the source of this expenditure financing. According to the organizational view the main bases to budget efficiency of territories is the financial independence of local authorities, which can be achieved through the effective decentralization. On the financial side, budgetary efficiency is the necessary financial resources to financing the current and development expenditure. This creates the preconditions for improving the territorial community’s development level, its competitiveness and quality of local resident’s life. In Ukraine the decentralization process has not provided the expected territories budget efficiency. There are such problems as lack of budget funds, miscalculations in the state and local taxation system, passive investment policy of local governments. The mechanism of the territories budget efficiency providing in the conditions of decentralization should includes the directions of increase of incomes and expenses efficiency, the corresponding the organizational, legal and institutional basis. It is important to provide the social and economic development of territories. The idea of forming the mechanism of territories budget efficiency is the improving the own financial policy of local self-governments. No qualitative changes are possible in condition of the passive financial and investment police of local governments. For the territories development it is important to stimulate the business activity, development of public-private partnership with the purpose to increasing of budget revenue. It is also necessary to increase the efficiency of formation, distribution and usage of budgetary recourses through the improvement of local budgets revenue and expenditure planning process. The best tools for this reason are economic and mathematic modeling. It will provide the concordance between the processes of formation and usage of territories financial resources and the main goals of local governments functioning and development. Through the mechanism of providing the territories budget efficiency in the context of decentralization it is possible to improve the policy of local financial management and achieve the territories socio-economic development.